2018
DOI: 10.1177/1687814017749705
|View full text |Cite
|
Sign up to set email alerts
|

Design and control of a diagnosis and treatment aimed robotic platform for wrist and forearm rehabilitation: DIAGNOBOT

Abstract: Therapeutic exercises play an important role in physical therapy and rehabilitation. The use of robots has been increasing day by day in the practice of therapeutic exercises. This study aims to design and control a novel robotic platform named DIAGNOBOT for diagnosis and treatment (therapeutic exercise). It has three 1-degree-of-freedom robotic manipulators and a single grasping force measurement unit. It is able to perform flexion-extension and ulnar-radial deviation movements for the wrist and pronation-sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The ability of the developed robotic system to perform therapeutic exercises is given in reference [24] along with the test studies with healthy subjects. In this study, the assessment and treatment suggestion performance of the controller was demonstrated through test studies conducted with 8 voluntary patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of the developed robotic system to perform therapeutic exercises is given in reference [24] along with the test studies with healthy subjects. In this study, the assessment and treatment suggestion performance of the controller was demonstrated through test studies conducted with 8 voluntary patients.…”
Section: Resultsmentioning
confidence: 99%
“…The assessment performance of the intelligent controller has been demonstrated through experiments which were performed with patients. The details on the design and conventional control structure of the system are given in previous studies [24,25].…”
Section: Reference Rom Force Evaluated Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The tendon-sheath concept has been widely used in medical and other types of robots [10][11][12][13] because of its high transmission precision, light weight, smooth transmission, flexibility, and small size. Kaneko et al 14,15 studied the transmission characteristics of a simple tendon-sheath model for finger joint control.…”
Section: Introductionmentioning
confidence: 99%
“…For patients after stroke, the task-repetitive training has been demonstrated to be effective in improving their upper and lower extremity functions and ADL [ 3 ]. To meet the requirement for repetitive training, various upper-limb rehabilitation robots have been developed over the past twenty years, which are generally classified into two categories [ 4 ]: end-effector robots, such as DIAGNOBOT [ 5 ], CARR [ 6 ], MIT-MANUS [ 7 ], MIME [ 8 ], GENTLE/s [ 9 ], and exoskeleton robots, such as CADEN-7 [ 10 ], RUPERT [ 11 ], BONES [ 12 ], and ARMin [ 13 ]. Since the robotic rehabilitation exhibits the advantages in terms of high-dosage, high-intensity, and task-specific training [ 14 ], randomized controlled trials comparing the robot-assisted and conventional therapy have yielded significant effects of robots on the improvements of limb function [ 15 , 16 ] and even ADL [ 17 ].…”
Section: Introductionmentioning
confidence: 99%